DEVELOPMENT OF TECHNOLOGY FOR WASTEWATER TREATMENT GENERATED DURING SILK PROCESSING AND THEIR REUSE IN THE PRODUCTION PROCESS (American Journal of Technology and Applied Sciences, 2024)
This article presents methods for the chemical analysis of wastewater composition, the development of wastewater treatment technology generated at cocoon production plants, and their reuse in the process of extracting silk fiber from cocoons.